CPW fed SRR loaded monopole antenna for triple band operations - Smitha K. M.; Aju John K. K.; Thomaskutty Mathew (Institute of Advanced Engineering and Science, 2020)
A planar CPW fed SRR loaded monopole antenna based on split ring resonator with triple-band operations is reported for passive UHF RFID, Wireless Local Area Networks (WLAN) and World Interoperability for Microwave Access (WiMAX) applications. Measured and simulated results show the effect of tapering of the SRR layer on bandwidth improvement and gain enhancement in comparison to monopole with SRR antenna. The CPW fed SRR loaded monopole antenna has a bidirectional pattern with high gain for wireless communication applications.